Non-Communicable Diseases in Jamaica : Moving from Prescription to Prevention - World Bank (Washington, DC, 2017)
Jamaica is a Caribbean country that has initiated comprehensive programs to address Non-Communicable Diseases (NCDs). The government created the National Health Fund (NHF) to reduce the cost of treatment of NCDs and finance some prevention programs. The main objective of this study is to learn from Jamaica's experience in tackling major NCDs and related risk factors, to provide policy options for Jamaica to improve its NCD programs and to share with other countries the lessons learned from its experience. The study attempts to answer three questions: a) whether the NHF and its drug subsidy program have reduced out-of-pocket spending on NCDs; b) whether access to treatment of NCDs has improved; and c) what the economic burden on NCD patients and their families is. The report presents an overall picture of the epidemiological and demographic transitions in Jamaica, its current burden of NCDs, and the change in the trend of NCDs in the past decade, using publicly available data, particularly data from the Jamaica living condition household surveys. It assesses the risk factors and analyzes Jamaica's response to NCDs with emphasis on the impact of the NHF on people's lives. Estimates of the economic burden of NCDs are provided and policy options to improve Jamaica's NCD programs are suggested. This study focuses on Jamaica's experience in addressing major NCDs and their related risk factors with the objective of learning from Jamaica and providing policy options to Jamaica to improve its programs.